Everybody's Business Is Nobody's Business : Or, Private Abuses, Public Grievances; Exemplified in the Pride, Insolence, and Exorbitant Wages of Our Women, Servants, Footmen, &c. - Defoe, Daniel, 1661?-1731 (Salt Lake City, UT : Project Gutenberg, 2000)
"Everybody's Business Is Nobody's Business" by Daniel Defoe is a pamphlet published in 1725. Writing under the pseudonym Andrew Moreton, Defoe addresses what he sees as problems with servant wages and labor relations in eighteenth-century England. The work examines "private abuses" and "public grievances," focusing particularly on domestic workers including women servants and footmen. Like many of Defoe's works, it was published anonymously to establish a particular point of view on social issues of the day. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Every-body%27s_Business,_Is_No-body%27s_Business
Release date is 2000-01-01
Transcribed from the 1889 George Bell & Sons edition by David Price
Keywords: Working class